Pegylated Interferon Alfa-2b Add-on Treatment in Hepatitis B Virus Envelope Antigen-Positive Chronic Hepatitis B Patients Treated with Nucleos(t)ide Analogue: A Randomized, Controlled Trial (PEGON). (17th March 2017) - Chi, Heng; Hansen, Bettina E.; Guo, Simin; Zhang, Ning Ping; Qi, Xun; Chen, Liang; Guo, Qing; Arends, Pauline; Wang, Ji-Yao; Verhey, Elke; de Knegt, Robert J.; Xie, Qing; et al.
Abstract: Background: We studied whether 48 weeks of pegylated interferon alfa-2b (peginterferon) add-on therapy increases serological response in hepatitis B virus (HBV) envelope antigen (HBeAg)–positive patients receiving nucleos(t)ide analogue (NA) therapy, compared with continued NA monotherapy. Methods: This randomized trial included HBeAg-positive patients with compensated liver disease who were treated with entecavir/tenofovir for >12 months and had an HBV DNA load of <2000 IU/mL. Patients were randomly assigned in a 1:1 ratio to 48 weeks of peginterferon add-on therapy (n = 39) or continued NA monotherapy (n = 38). Response (defined as HBeAg seroconversion with an HBV DNA load of <200 IU/mL) was assessed at week 48, with responders discontinuing NA therapy at week 72. Results: The primary end point (response at week 96) was achieved in 18% of patients who were assigned peginterferon add-on therapy versus 8% of patients assigned NA monotherapy ( P = .31). Among 58 interferon-naive patients, add-on therapy led to a greater frequency of HBeAg seroconversion (30% vs 7%; P = .034) and response (26% vs 7%; P = .068) at week 96, compared with monotherapy. Among 8 responders at week 48 who discontinued NA therapy at week 72, 6 patients (75%) maintained a response until week 96 (4 of 6 [67%] in the add-on therapy group vs 2 of 2 [100%] in the monotherapy group; P = 1.00). Adverse events were mainly related to peginterferon. Conclusion: The primary end point was negative, but peginterferon add-on therapy appeared to result in a greater frequency of HBeAg seroconversion, compared with NA monotherapy, in interferon-naive patients receiving NA therapy. Clinical Trials Registration: NCT01532843.